Rhetoric on Language and Truth from Modernity to Postmodernity - Bhusal, Purna Chandra (Gipan, 2025)
In this article, I examine the changing perspectives on language and truth when rhetoric transitions from modernity to postmodernity, revolving around the perspectives of five thinkers: John Locke, Giambattista Vico, Friedrich Nietzsche, Jacques Derrida, and Michel Foucault. To do so, I synthesize the history of rhetoric, trace a conceptualization of modernity and postmodernity, and analyze the arguments of the five thinkers from a comparative perspective. The comparative analysis suggests that Locke distinguishes between the philosophical use of language and its rhetorical (ab)use, grounding truth in sense perception. Vico expands this notion by asserting that language communicates reason and imagination, positioning truth as a synthesis of both faculties. Nietzsche challenges traditional epistemologies by viewing language as inherently metaphorical and truth as an anthropomorphic illusion. Derrida deconstructs the idea of absolute truth, emphasizing the provisional and unstable nature of language, where meaning is always deferred. Finally, Foucault situates language within power structures, arguing that truth is constructed, institutionalized, and disseminated through discourse. By tracing these conceptual shifts, this study highlights the interplay between language and truth, demonstrating how rhetorical and philosophical perspectives shift and change over time (de)establishing the human way of thinking.